Comparison of Therapeutic Efficacy of Topical Tacrolimus 0.1% and Topical Dithranol 0.5% in Treatment of Alopecia Areata - Husain, Majid; Siddiqui, Muhammad Adeel; Mazhar, Hina; Sheikh, Zafar; ., Adiba; Yasmeen, Kashifa (Pakistan Armed Forces Medical Journal, 2025)
Objective: To compare the therapeutic efficacy of topical Tacrolimus 0.1% and topical Dithranol 0.5% in patients of alopecia areata.Study Design: Quasi Experimental Study Place and Duration of Study: Departments of Dermatology, Combined Military Hospital, Hyderabad and Combined Military Hospital, Abbottabad from Sep 2019-2020.Methodology: Patients fulfilling the inclusion criteria were selected in the first 1 and a half months, after written informed consent. The patients were divided into two Groups A and B, by lottery method. Group A received topical Tacrolimus 0.1% application twice a day and Group B received topical Dithranol 0.5% application twice a day, for 24 weeks. The response of treatment was calculated by two observers and each of them determined the percentage of hair re growth by comparing the pre and post treatment photographs of the patient at 24 weeks.Results: More than 80% Hair re - growth was observed in 7(23.33%) of the patients in Tacrolimus Group and 12(40%) of the patients in Dithranol Group.  Therapeutic efficacy of Dithranol was more than Tacrolimus as their comparison revealed p value=0.039.Conclusion: Therapeutic efficacy of Dithranol is superior to Tacrolimus in treatment of alopecia areata.